ROLE OF HOLOCAUST IN GERMAN-ISRAELI RELATIONS - K. Y. Khderi (Vestnik MGIMO-Universiteta)
Relations between Berlin and Tel Aviv are unique. They occupy a special place in the foreign relations of Germany because of the "historic responsibility" o f the Germans for the Holocaust - the genocide of 6 million Jews during the time of National Socialism. The Germans certainly learned a lesson from its past. For 70 years they have been demonstrating to the entire world its good intentions, and did everything possible in order to atone for the suffering of Jews. Today, among the Germans one can observe some fatigue of the theme. There is an increasing desire to leave the topic in the past and to develop relations with Israel, which is not based on the need to make concessions because of the fear of being convicted of a tragic chapter in the history. The same cannot be said about the Jews, who do not forget to remind Berlin about its "special historical responsibility." We can assume that in the short and medium term, the Holocaust will determine the development of relations between Berlin and Tel Aviv.